2011
DOI: 10.1002/psc.1316
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from Royal Jelly: studies on the antimicrobial activity of jelleins, jelleins analogs and synergy with temporins

Abstract: Peptides isolated from natural fonts are the object of several studies aimed at finding new molecules possessing antibacterial activity. We focused our studies on peptides originally isolated from the Royal Jelly, the jelleins and on some analogs having a UV reporter at the N- or C-terminus. We found that jelleins are mainly active against gram-positive bacteria; interestingly, they act in synergy with peptides belonging to the family of temporins such as temporin A and temporin B against Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 24 publications
1
79
0
Order By: Relevance
“…For example, mammalian cationic AMPs act synergistically against bacteria including antibiotic-resistant Staphylococcus aureus strains [68]. But synergistic effects have been reported across a wide range of taxa, including oysters [36], beetles [49], hemiptera [69], honeybees [39], bumblebees [43], humans [70] and plants [71]. Often, in these studies, the effect is tested against bacteria, and in some cases, the synergy is observed with regard to effectors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mammalian cationic AMPs act synergistically against bacteria including antibiotic-resistant Staphylococcus aureus strains [68]. But synergistic effects have been reported across a wide range of taxa, including oysters [36], beetles [49], hemiptera [69], honeybees [39], bumblebees [43], humans [70] and plants [71]. Often, in these studies, the effect is tested against bacteria, and in some cases, the synergy is observed with regard to effectors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Royal Jelly is a hive product rich in bioactive compounds with various biological properties and effects: antioxidative (Guo et al, 2005(Guo et al, , 2009Jamnik et al, 2007;Silici et al, 2009; DelkhosheKasmaie et al, 2014), antiaging (Inoue et al, 2003), tonic (Fossati, 1972), antimicrobial (Fontana et al, 2004;Romanelli et al, 2011), immunomodulatory (Mannoor et al, 2009), anti-inflammatory (Kohno et al, 2004(Kohno et al, , 2015, neurotrophic, hypoglicaemic, hypocholesterolaemic (Kamakura et al, 2006;Kashima et al, 2014), vasodilative (Tokunaga et al, 2004), antitumoral, anti-allergic (Okamoto et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One potential solution to the problems of both resistance and toxicity is to use a synergistic combination of antimicrobial compounds, an approach that is ubiquitous in anticancer therapy and is receiving increasing attention in the treatment of infectious diseases (2). Many species produce AMPs with known synergistic interactions, including bacteria (14), insects (20), amphibians (16,31), and humans (3,27,28), with synergy arising through a variety of mechanisms (2,14,29).…”
mentioning
confidence: 99%